(8x+2)(9x+3)+x=180

Simple and best practice solution for (8x+2)(9x+3)+x=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x+2)(9x+3)+x=180 equation:


Simplifying
(8x + 2)(9x + 3) + x = 180

Reorder the terms:
(2 + 8x)(9x + 3) + x = 180

Reorder the terms:
(2 + 8x)(3 + 9x) + x = 180

Multiply (2 + 8x) * (3 + 9x)
(2(3 + 9x) + 8x * (3 + 9x)) + x = 180
((3 * 2 + 9x * 2) + 8x * (3 + 9x)) + x = 180
((6 + 18x) + 8x * (3 + 9x)) + x = 180
(6 + 18x + (3 * 8x + 9x * 8x)) + x = 180
(6 + 18x + (24x + 72x2)) + x = 180

Combine like terms: 18x + 24x = 42x
(6 + 42x + 72x2) + x = 180

Reorder the terms:
6 + 42x + x + 72x2 = 180

Combine like terms: 42x + x = 43x
6 + 43x + 72x2 = 180

Solving
6 + 43x + 72x2 = 180

Solving for variable 'x'.

Reorder the terms:
6 + -180 + 43x + 72x2 = 180 + -180

Combine like terms: 6 + -180 = -174
-174 + 43x + 72x2 = 180 + -180

Combine like terms: 180 + -180 = 0
-174 + 43x + 72x2 = 0

Begin completing the square.  Divide all terms by
72 the coefficient of the squared term: 

Divide each side by '72'.
-2.416666667 + 0.5972222222x + x2 = 0

Move the constant term to the right:

Add '2.416666667' to each side of the equation.
-2.416666667 + 0.5972222222x + 2.416666667 + x2 = 0 + 2.416666667

Reorder the terms:
-2.416666667 + 2.416666667 + 0.5972222222x + x2 = 0 + 2.416666667

Combine like terms: -2.416666667 + 2.416666667 = 0.000000000
0.000000000 + 0.5972222222x + x2 = 0 + 2.416666667
0.5972222222x + x2 = 0 + 2.416666667

Combine like terms: 0 + 2.416666667 = 2.416666667
0.5972222222x + x2 = 2.416666667

The x term is 0.5972222222x.  Take half its coefficient (0.2986111111).
Square it (0.08916859567) and add it to both sides.

Add '0.08916859567' to each side of the equation.
0.5972222222x + 0.08916859567 + x2 = 2.416666667 + 0.08916859567

Reorder the terms:
0.08916859567 + 0.5972222222x + x2 = 2.416666667 + 0.08916859567

Combine like terms: 2.416666667 + 0.08916859567 = 2.50583526267
0.08916859567 + 0.5972222222x + x2 = 2.50583526267

Factor a perfect square on the left side:
(x + 0.2986111111)(x + 0.2986111111) = 2.50583526267

Calculate the square root of the right side: 1.582983027

Break this problem into two subproblems by setting 
(x + 0.2986111111) equal to 1.582983027 and -1.582983027.

Subproblem 1

x + 0.2986111111 = 1.582983027 Simplifying x + 0.2986111111 = 1.582983027 Reorder the terms: 0.2986111111 + x = 1.582983027 Solving 0.2986111111 + x = 1.582983027 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.2986111111' to each side of the equation. 0.2986111111 + -0.2986111111 + x = 1.582983027 + -0.2986111111 Combine like terms: 0.2986111111 + -0.2986111111 = 0.0000000000 0.0000000000 + x = 1.582983027 + -0.2986111111 x = 1.582983027 + -0.2986111111 Combine like terms: 1.582983027 + -0.2986111111 = 1.2843719159 x = 1.2843719159 Simplifying x = 1.2843719159

Subproblem 2

x + 0.2986111111 = -1.582983027 Simplifying x + 0.2986111111 = -1.582983027 Reorder the terms: 0.2986111111 + x = -1.582983027 Solving 0.2986111111 + x = -1.582983027 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.2986111111' to each side of the equation. 0.2986111111 + -0.2986111111 + x = -1.582983027 + -0.2986111111 Combine like terms: 0.2986111111 + -0.2986111111 = 0.0000000000 0.0000000000 + x = -1.582983027 + -0.2986111111 x = -1.582983027 + -0.2986111111 Combine like terms: -1.582983027 + -0.2986111111 = -1.8815941381 x = -1.8815941381 Simplifying x = -1.8815941381

Solution

The solution to the problem is based on the solutions from the subproblems. x = {1.2843719159, -1.8815941381}

See similar equations:

| (8x+2)(9x+3)+x=q | | 5-.66666666n=7 | | 64-7x=11x+18 | | 2x+2=40 | | 8log(x+3)=10 | | 1-3x+8x=3+5x | | 4x+-2=6 | | -16y=0 | | 3(m-9)= | | 3x(x-12)=0 | | (x^2-x+.25)=(.3+x) | | 8-4(m+5)= | | X+2=3x+2-2x | | a^4-12a^2+35=0 | | 6a(2a-1)-(3a^2-3a)= | | -8x=4 | | n-15=30 | | -30-5m=-4(m+7) | | 8x^2-11x+3=0 | | 27=17-2y | | -2=2x+10 | | 26+4a=6a | | 35x^2+56x+21=0 | | 4s=76 | | 10x-3(x-6)=11+30 | | x^2+y^2-2x+14y+14=0 | | C=0.4t+1 | | 3(x+2)-5=10x-3 | | q-11=74 | | 2x-15=x+30 | | -2(r+7)=r+1 | | A=(3Y+1)*27 |

Equations solver categories